Advances in Biology and Treatment of Glioblastoma - Somasundaram, Kumaravel (Current Cancer Research,, 2017)
This volume covers the most important areas of glioblastoma - surgical resection, molecular pathology, targeted therapies, cancer stem cells, the role of DNA methylation, targeted sequencing for personalized therapy, animal models and advances in pediatric glioblastoma. Chapter authors are junior and senior investigators, who are well established in their particular areas and include neurosurgeons, neuropathologists, neurooncologists and basic scientists. .